2020
DOI: 10.1155/2020/9525179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Rutting Performance of the Field Specimen Using the Hamburg Wheel‐Tracking Test and Dynamic Modulus Test

Abstract: Rutting is a major distress occurring in the service life of the asphalt pavement, especially in hot weather areas. A laboratory-produced specimen is widely used for rutting performance evaluation which may not be completely represented by the field situation. The objective of this study is to evaluate the rutting performance of field specimens from the Chongqing highway by utilizing the Hamburg wheel-tracking test (HWTT) and dynamic modulus test. Different test conditions were conducted on the HWTT by investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Asphalt pavement during service life is prone to crack and damage due to heavy load, overload, high temperature, and water erosion, resulting in rutting disease and affecting its driving comfort and safety [1,2]. en, the further development of rutting will also cause other diseases such as network cracks and pits, which will seriously reduce the structural performance and service performance of asphalt pavement [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt pavement during service life is prone to crack and damage due to heavy load, overload, high temperature, and water erosion, resulting in rutting disease and affecting its driving comfort and safety [1,2]. en, the further development of rutting will also cause other diseases such as network cracks and pits, which will seriously reduce the structural performance and service performance of asphalt pavement [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Rutting is one of the main early distresses in asphalt pavements, which not only significantly reduces the service quality and service life of the road but also poses a serious threat to the driving of the vehicle [1][2][3]. rough investigation, it was found that bad construction quality of the asphalt layer is one of the main reasons for the early distresses in asphalt pavement [4,5].…”
Section: Introductionmentioning
confidence: 99%